A Review of Biofouling of Ships’ Internal Seawater Systems - Davidson, Ian; Cahill, Patrick; Hinz, Arne; Kluza, Daniel; Scianni, Chris; Georgiades, Eugene (Frontiers in Marine Science, 2021)
Internal seawater systems (ISS) are critical to the proper functioning of maritime vessels. Sea water is pumped on board ships for a broad array of uses, primarily for temperature control (e.g., engine and electrical systems), cooling capacity (e.g., air conditioners and refrigeration), and water provision (e.g., drinking, firefighting, steam, and ballast). Although sea water may spend only a brief period within ISS of a vessel, it can carry microorganisms and larval stages of macroorganisms throughout the system leading to biofouling accumulation that can impair system function or integrity. ISS can also act as a sub-vector of species translocations, potentially facilitating biological invasions. This review describes ships’ ISS with a focus on operational impacts of biofouling and current drivers and barriers associated with ISS biofouling management. As ISS internal components are difficult to access, reports and studies of ISS biofouling are uncommon and much of the dedicated literature is decades old. The impact of biofouling on ISS and vessel operations is based on increased surface roughness of pipework and equipment, restricted water flow, corrosion and subsequent component impingement, reduced surface functional efficiency, and potential contamination by pathogens that can affect human and aquatic animal health. Biofouling management is primarily achieved using antifouling coatings and marine growth protection systems, but independent and accessible data on their efficacy in ISS remain limited. Further research is required to resolve the extent to which biofouling occurs in ISS of the modern commercial fleet and the efficacy of preventive systems. Such information can ultimately inform decisions to improve operational efficiency for vessel operators and ensure any biosecurity risks are appropriately managed.